2005
DOI: 10.1520/jfs2005023
|View full text |Cite
|
Sign up to set email alerts
|

Virtopsy: Postmortem Minimally Invasive Angiography Using Cross Section Techniques—Implementation and Preliminary Results

Abstract: Postmortem investigation is increasingly supported by Computed Tomography (CT) and Magnetic Resonance Imaging (MRI). This led to the idea to implement a noninvasive or minimally invasive autopsy technique. Therefore, a minimally invasive angiography technique becomes necessary, in order to support the vascular cross section diagnostic. Preliminary experiments investigating different contrast agents for CT and MRI and their postmortem applicability have been performed using an ex-vivo porcine coronary model. MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 120 publications
0
79
1
5
Order By: Relevance
“…[31][32][33][34] In porcine exvivo experiments distribution defects of injected gadolinium could be simulated within the porcine myocardium, which possibly can be correlated to a disturbed antemortem perfusion as well. 31 A combination of pmMRI and minimally invasive angiography will enhance the diagnostic performance of pm imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] In porcine exvivo experiments distribution defects of injected gadolinium could be simulated within the porcine myocardium, which possibly can be correlated to a disturbed antemortem perfusion as well. 31 A combination of pmMRI and minimally invasive angiography will enhance the diagnostic performance of pm imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The first systematic research was started in 2004 in the Institute of Legal Medicine in Bern, Switzerland, in the context of the Virtopsy® project. 28 In 2005, Jackowski et al 29 reported preliminary results of a new technique of minimally invasive whole-body PMCTA using a cannulation of the femoral vessels on one side of the body and the injection of meglumine ioxithalamate as a contrast agent. At the same time and same place, first experiments started with a dynamic angiographic analysis of a whole body.…”
Section: Post-mortem Angiography Goes Forensic Imaging-introduction Omentioning
confidence: 99%
“…Estos procedimientos han sido utilizados en Tanatología, Patología y Traumatología Forenses [5,6,7,8,9,10,11]. En Histopatología, su utilización se ha extendido desde la morfometría de diferentes estructuras [12] hasta sofisticadas aplicaciones en citogenética [13].…”
Section: Técnicas De Virtopsiaunclassified